The Internalization of The Values of Freedom to Learn in the Learning of Islamic Religious Education (PAI) at Public Senior High School (SMAN) 1 of Wanasaba in the Academic Year of 2023/2024 - Jumaah, Jumaah; Masnun, Masnun; Supardi, Supardi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
The research aimed to investigate the internalization process of the value of freedom in learning within the context of Islamic Religious Education at Public Senior High School (SMAN) 1 Wanasaba during the academic year 2023/2024. Freedom in learning encourages student autonomy and active participation in their educational journey. Additionally, it sought to assess the implementation of this concept within the Islamic Religious Education curriculum. Employing a qualitative approach with a case study method, data were gathered through interviews, classroom observations, and document analysis. Findings revealed the successful integration of the freedom to learn concept in Islamic Religious Education at SMAN 1 Wanasaba, with Islamic values deeply ingrained in the learning process. Teachers played pivotal roles as exemplars in fostering the internalization of this value.This study contributes to understanding how freedom in learning principles can be effectively applied within Islamic Religious Education, underscoring the crucial role of teachers in facilitating value internalization. Moreover, it underscores the significance of incorporating religious values into active, participatory educational methodologies, highlighting the pivotal role of Religious Education in character development. In summary, this research enhances comprehension of learning methodologies aligned with Islamic Religious Education principles, emphasizing the importance of teacher guidance in nurturing students' character development through active learning approaches.